Windows to Linux migration toolkit - Allen, David; Lahti, Christian (Rockland, MA : Syngress Pub. ; [Sebastopol, CA] : Distributed by O'Reilly Media in the United States and Canada, 2004)
This book will teach people how to migrate systems from Windows to Linux. It provides migration process planning, automated migration scripts, anti-virus / anti-spam solutions, and specific migration and deployment details for all relevant technologies. IT professionals who wish to maximize the value of their Windows to Linux migration services will find this book valuable. The book will help them fine-tune their migration services to make them more efficient, thorough, feature-enhanced, and cost-effective by utilizing migration scripts and best practices gleaned from the author's many years of real-world migrations in large and small companies. * The book and fully functioning scripts on the CD-ROM work for migrations from Windows NT or Windows 2000 to any Linux distribution. * David Allen has done over 25,000 user migrations from Windows to Linux. * Microsoft will stop supporting Windows NT in December 2004 forcing over 2 million enterprise customers to migrate from Windows NT to a new sever operating system. Both IBM and Dell are offering enterprise servers running Linux which will allow customers to realize a 50% reduction in TCO. In 2003 Linux servers represented the largest growth segment in the Server market, and all the major research groups indicate this trend will continue through t least 2007.
Network services migration roadmap -- Core TCP/IP networking services -- Directory services -- Authentication services -- File services -- Print services -- Messaging services -- Groupware and calendaring services -- Web ServicesIIS vs Apache -- Desktop migration roadmap -- Inside the typical Linux desktop.
Includes index.
Keywords: Systems migration -- Handbooks, manuals, etc; Operating systems (Computers) -- Handbooks, manuals, etc; Linux. -- Handbooks, manuals, etc; Microsoft Windows (Computer file). -- Handbooks, manuals, etc; Electronic books